Unveiling Gender Portrayals in Indonesian EFL textbooks: A Critical Discourse Analysis - Susanto, Susanto; Chojimah, Nurul (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2024)
This study aims to describe the representation of genders in five Indonesian EFL textbooks published by Erlangga Publishing and unveil the ideology and attitudes behind the image of genders. The methods of critical discourse analysis (CDA) proposed by Van Dijk, which comprise discourse, social cognition, and discourse and society, are used to unveil the patterns of gender portrayal and the attitudes behind it. Data for this study are the human images in five Indonesian EFL textbooks published by Erlangga Publishing. This study reveals that in terms of frequency, women are more dominant than men; women’s images appear more frequently than men's. In dealing with other aspects under study, men and women are depicted symmetrically. The symmetrical representation between men and women suggests the attitude and ideology of gender equality the authors uphold.